Tender pricing of infrastructure projects: Affecting factors - Tayeh, B.A. (American Society of Civil Engineers (ASCE), 2019)
Infrastructure projects are what keep the important functions of any state alive. This paper is about a study concerning the factors affecting the tender pricing for infrastructure projects. A questionnaire was designed according to the collected factors form the literature, which were classified into six clusters (owner, consultant, contractor, donor, market, and project). The final version of the questionnaire was distributed to the owners, constructors, and consultants after the pilot study. The analysis shows that: the highest cluster is consultant related with RII of 81.33. The second cluster is donor related cluster with RII of 79.92. On the other hand, the highest two factors from the contractor cluster are: contractor visits to the project site, and study tender documents accurately, with RII 88.33 and 86.67, respectively. It can be recommended that the contractor should be aware of the conditions of the project site, and the nature of the soil, taking into account the different nature of the land from one location to another, knowing that the rocky land requires a high cost and a longer period of time to complete the work. Also contract terms and the executive regulations should be accurately reviewed, which may bear additional costs. Â© 2019 American Society of Civil Engineers.